Demand Analysis of Rice in Nigeria: Application of Quadratic almost Ideal Demand System Model - Onyeneke, Robert Ugochukwu; Emenekwe , Chukwuemeka Chinonso; Amadi, Mark Umunna; Munonye, Jane Onuabuchi; Njoku, Chukwudi Loveday; Izuogu, Chibuzo Uzoma (Asian Journal of Agriculture and Rural Development, 2020)
The paper analyzed the demand for imported rice, local rice, maize, and other cereals in Nigeria. Using the second wave data of the Nigerian Living Standard Measurements Survey - Integrated Survey on Agriculture, it employed the Quadratic Almost Ideal Demand System model for empirical analysis. The result indicates that the imported and local rice are proved to be normal goods. However, imported rice is a luxury item while local rice is a necessity. The compensated and uncompensated own-price elasticities for imported and local rice are negative, indicating that an increase in own-price will decrease its own-demand in line with the law of demand. The estimates of uncompensated cross-price elasticity show that imported rice and local rice are complements in Nigeria. Finally, the study represents an effort to disaggregate food demand analysis to obtain useful information on price and other factors determining the demand for specific foods.